Idiosyncratic Risk, Economic Activity, and Sectoral Growth: Structural Linkages with Inflation, SDGs Affordability, and Economic Performance in Asian Economies - Asri, Marselinus (Jurnal Ilmiah Multidisipin, 2025)
This study investigates the structural relationships between idiosyncratic risk, economic activity, sectoral GDP output, inflation, Sustainable Development Goals (SDGs) affordability, and economic growth in selected Asian economies. Using Structural Equation Modeling (SEM), the research analyzes how sector-specific risks and macroeconomic factors influence economic performance. Data on macroeconomic indicators, sectoral output, and risk measures were collected from official statistical agencies and international financial databases. The model results reveal that idiosyncratic risk exerts a strong positive and significant influence on sectoral GDP, suggesting that sector-specific volatility may foster growth opportunities or higher returns. However, idiosyncratic risk does not have a significant direct effect on overall economic activity. Economic activity is shown to significantly influence both sectoral GDP and economic growth, underscoring its role as a central driver of economic performance. The analysis also reveals a strong negative effect of SDGs affordability on sectoral GDP, indicating potential short-term trade-offs between sustainability investments and sectoral output. Inflation demonstrates a moderate positive and significant effect on GDP sector performance, suggesting that controlled price increases may stimulate production and investment. Conversely, GDP sector output does not have a significant direct impact on overall economic growth, implying that sector-specific output gains require complementary macroeconomic mechanisms to translate into broad-based growth. These findings highlight the complex interplay between risk, macroeconomic policy, and sustainability objectives, offering valuable insights for policymakers seeking to balance growth, stability, and sustainable development.